2018
DOI: 10.1186/s12944-018-0689-5
|View full text |Cite
|
Sign up to set email alerts
|

Lipid profiles in French West Indies sickle cell disease cohorts, and their general population

Abstract: BackgroundThe pathophysiology of sickle cell disease (SCD) and the variability of its clinical expression remain not fully understood, whether within or between different SCD genotypes. Recent studies have reported associations between lipid levels and several SCD complications. If lipid levels have been previously described as low in sickle cell anemia (SCA), few data have been provided for sickle cell SC disease (SCC). We designed our epidemiological study to isolate lipid levels and profiles by genotype in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 41 publications
3
14
0
Order By: Relevance
“…Our findings are in agreement with previous laboratory profile of HbSC disease [26], including increased creatinine levels [27] and increased total cholesterol, HDL-C and LDL-C as well as decreased NOm determinations [8]. This lipid profile among HbSC individuals has also been show in other populations [28].…”
Section: Discussionsupporting
confidence: 92%
“…Our findings are in agreement with previous laboratory profile of HbSC disease [26], including increased creatinine levels [27] and increased total cholesterol, HDL-C and LDL-C as well as decreased NOm determinations [8]. This lipid profile among HbSC individuals has also been show in other populations [28].…”
Section: Discussionsupporting
confidence: 92%
“…Lipid profile and anthropometrics, two factors that are associated with T2D pathogenesis, also differ between SCA and HbSC disease. A recent study (Lalanne‐Mistrih et al , ) showed that SCA and HbSC subjects had distinct lipid profiles that also differed from the general population. Notably, SCA subjects had higher triglyceride levels, which were associated with ACS, while non‐high density lipoprotein‐cholesterol levels were associated with osteonecrosis in HbSC subjects (Lalanne‐Mistrih et al , ).…”
mentioning
confidence: 99%
“…A recent study (Lalanne‐Mistrih et al , ) showed that SCA and HbSC subjects had distinct lipid profiles that also differed from the general population. Notably, SCA subjects had higher triglyceride levels, which were associated with ACS, while non‐high density lipoprotein‐cholesterol levels were associated with osteonecrosis in HbSC subjects (Lalanne‐Mistrih et al , ). Furthermore, obesity has been shown to be on the rise in people with SCD, particularly in those with HbSC (Ballas, ).…”
mentioning
confidence: 99%
See 2 more Smart Citations